Τυμβωρῦχοι καὶ σκυλευτἐς νεκρῶν: Οι απόψεις του Νικολάου Καταφλώρον για τη ρητορική και τους ρήτορες στην Κωνσταντινούπολη του 12ου αιώνα - ΛΟΥΚΑΚΗ, Μαρίνα (Byzantina Symmeikta, 2008)
Marina Loukaki Τυμβωρῦχοι and σκυλευτὲς νεκρῶν: The views of Nicolaos Kataphloron on rhetoric and the rhetoricians in 12th century Constantinople There were many factors that were conducive to the flourishing of rhetoric in Constantinople during the Comneni and Angeli era. In the preface of an unpublished encomium about a Greek governor, Nikolaos Kataphloron, 12th century maistor of the rhetors and oikoumenikos didaskalos, criticizes the rhetors of his time, without excepting himself, for being occupied in their works, excessively and exclusively, with the word elegance. He particularly rebukes 12 most prolific writers of Constantinople, whose compositions are indeed patchworks of borrowings from ancient literature. These plagiarists, by shamelessly exhibiting their plunder to the public, gain for themselves fame and renown. Our commentary of the passage demonstrates that Kataphloron's views are greatly influenced by the discussion on the worth of rhetoric, which started in antiquity and was resumed by the writers of the Second Sophistic. However, it is interesting to note that Kataphloron reproaches -in a humorous way- 12 specific rhetors, who are not any others but the 12 didaskaloi of the Patriarchate. It is also pointed out that Michael Choniates expresses similar views some years later.